(untitled) (Iraqi Journal of Medical Sciences, 2024)
Background: A novel coronavirus causing corona virus 2019 (COVID-19) disease, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was a serious cause of respiratory failure, cytokine release syndrome or myocarditis. The immune checkpoint blockade (ICB), cytotoxic T-lymphocyte associated proteins 4 (CTLA-4) and programmed cell death protein 1 / programmed death-ligand 1(PD-1)/PD-L1) axis, has been a recognized standard of treatment in various cancers and in the prevention of several viral infections. Objective: To evaluate soluble immune checkpoint levels (PD-1, PDL-1 and CTLA-4) in SARS-Cov-2 patients. Methods: This cross-sectional study included 90 patients with confirmatory SARS-CoV-2 test by polymerase chain reaction (PCR), as they were seeking for treatment at Medical City in Baghdad’s Teaching Hospital (BTH). Patients with SARS-Cov-2 were divided into two groups: first group were those with severe SARS-CoV-2 symptoms lowest oxygen saturation (less than 90% O2 saturation) and the second group are those with mild-moderate SARS-CoV-2 symptoms. The three ml of venous blood were taken from each patient to evaluate the levels of soluble PDL-1, PD-1, and CTLA-4 by using enzyme linked immunological sorbent test (ELISA). Results: Data regarding serum level of CTLA-4, PD-1 and PD-L1 in mild-moderate and severe covid-19 patients were found to be abnormally distributed. The median serum level of CTLA-4, PD-1 and PD-L1 in mild-moderate groups was much lower than that of severe cases with highly significant differences. Age demonstrated a positive significant correlation with each of CTLA-4, PD-1 and PD-L1. Soluble CTLA-4 had a positive significant correlation with each of PD-1 and PD-L1. Finally, PD-1 had a positive significant correlation with PD-L1. Conclusion: Soluble immune checkpoint markers are significantly increased in patients with severe covid-19 cases and soluble immune checkpoint markers are positively significant correlated with age. Keywords: Immune checkpoint, CTLA-4, PD1, PDL-1, SARS-C0v-2, COVID-19 Citation: Talib AL, Kadhim HS. The role of soluble immune checkpoint in SARS-CoV-2 Iraqi patients. Iraqi JMS. 2024; 22(2): 268-273. doi: 10.22578/IJMS.22.2.11